Green magnetic wave absorber, the potential of paddy straw and recycled paper - Munawar, Rose Farahiyan; Shahril, M. Khairul; Abu, Maisarah; Bani Hashim, Ahmad Yusairi (Maney Publishing, 2014)
Earlier,magnetic cellulose fibre was successfully produced by lumen loading and in situ coprecipitation methods.But never before had magnetic paper or magnetic sheets been produced from paddy straw and recycled paper as their substrates.The main properties needed to produce these green magnetic sheets are natural fibres possessing lumen,a hollow cylindrical shape along the fibres. Although magnetic particles can be introduced outside of this lumen,it interferes with inter-fibre bonding,leading to low-grade paper properties and making loading processes very crucial.This journal describes the properties of paddy straw and recycled paper in terms of lumen possession and the lumen's ability to be loaded with magnetic particles.The results obtained show that when using lumen,the loading technique is better than that using the in situ coprecipitation method,and paddy straw has better magnetic particle loading ability than recycled paper.